Boron, Copper, and Zinc Affect the Productivity, Cup Quality, and Chemical Compounds in Coffee Beans - Junia Maria Clemente; Herminia Emilia Prieto Martinez; Adriene Woods Pedrosa; Yonara Poltronieri Neves; Paulo Roberto Cecon; John Lonfover Jifon (Journal of Food Quality)
Micronutrients perform specific and essential functions in plant metabolism, and their deficiency may lead to metabolic disturbances that affect coffee production and quality beverage. In Brazil, the B, Cu, and Zn are the main micronutrients, and these are provided by soil or foliar fertilization, frequently with low recovery efficiency. This work objected verifying the feasibility of supplying of B, Cu, and Zn via insertion of tablets in the orthotropic branch of Coffea arabica, as well as to evaluate the coffee plant response in terms of productivity and quality of the beverage. Adult plants received B, Cu, and Zn, each micronutrient alone or combined with the other two, by foliar fertilization or by tablets inserted in the trunk base. The productivity, cupping quality, and some chemical indicators of beans quality were evaluated in two crop seasons. Boron, copper, and zinc supplied by foliar spray or solid injections in the trunk influenced the chemical composition and quality of the coffee beans, characterized by the cupping test and the levels of caffeine, trigonelline, sucrose, glucose, arabinose, mannose, 3-caffeoylquinic acid, 5-caffeoylquinic acid, polyphenol oxidase activity, and total phenolic compounds. Copper and zinc were equivalent in either form of supply regarding the production and quality of coffee.